Family Communication about Donor Conception: A Qualitative Study with Lesbian Parents - Van Parys, Hanna; Wyverkens, Elia; Provoost, Veerle; De Sutter, Petra; Pennings, Guido; Buysse, Ann (Family process, 2016)
In this qualitative study of 10 lesbian couples who built their families through anonymous donor conception, we explore how lesbian parents experience communication about the donor conception within the family. While for these families “disclosure” of donor conception is often seen as evident, the way parents and children discuss this subject and how this is experienced by the parents themselves has not received much research attention. To meet this gap in the literature, in‐depth interviews with lesbian couples were conducted. An Interpretative Phenomenological Analysis showed that this family communication process can be understood within the broader relational context of parent–child relationships. Even though parents handled this family communication in many different ways, these were all inspired by the same motives: acting in the child's best interest and—on a more implicit level—maintaining good relations within the family. Furthermore, parents left the initiative for talking about the DC mostly to the child. Overall, parents aimed at constructing a donor conception narrative that they considered acceptable for both the children and themselves. They used different strategies, such as gradual disclosure, limiting the meaning of the donor, and justifying the donor conception. Building an acceptable donor conception narrative was sometimes challenged by influences from the social environment. In the discussion, we relate this qualitative systemic study to the broader issues of selective disclosure and bidirectionality within families. En este estudio cualitativo de diez parejas de lesbianas que construyeron sus familias mediante la concepción por donante anónimo, analizamos cómo las madres lesbianas viven la comunicación acerca de la concepción por donante dentro de la familia. Si bien para estas familias la “revelación” de la concepción por donante generalmente se considera obvia, la manera en la que los padres y los hijos debaten este tema y la forma en la que los padres viven esto no ha recibido mucha atención en el área de la investigación. Para cerrar esta brecha en la bibliografía existente, se realizaron entrevistas detalladas con parejas de lesbianas. Un análisis fenomenológico interpretativo indicó que este proceso de comunicación familiar puede comprenderse dentro del contexto relacional más amplio de las relaciones padre/madre‐hijo. Aunque las madres manejaron esta comunicación familiar de varias maneras diferentes, todas estas estuvieron inspiradas por los mismos objetivos: actuar en beneficio del niño – a un nivel más implícito – manteniendo las buenas relaciones dentro de la familia. Además, las madres prácticamente le dejaron la iniciativa de hablar acerca de la concepción por donante al niño. En general, las madres pretendieron elaborar una narrativa sobre la concepción por donante que consideraran aceptable tanto para los niños como para ellas mismas. Utilizaron diferentes estrategias, por ejemplo, la revelación gradual, la limitación del significado de donante y la justificación de la concepción por donante. La elaboración de una narrativa aceptable acerca de la concepción por donante fue a veces cuestionada por influencias del entorno social. En el debate, relacionamos este estudio sistémico cualitativo con los asuntos más amplios de revelación selectiva y bidireccionalidad dentro de las familias. 在这项有关10对通过匿名捐献者受孕的女同性恋伴侣的定性研究中,我们探讨了女同性恋家长在家庭中就通过捐献者受孕这一问题的沟通体验。对这些家庭而言,其通过捐献者受孕这一事实的'披露'是显然的,然而关于家长和孩子讨论这一话题的方式和家长自己是如何经历这个过程的研究还不多。为了补充这方面文献的空白,我们对女同性恋伴侣进行了深入采访。一项解释性现象分析显示家庭沟通过程可以在家长‐孩子关系这一更广的关系背景下被认识理解。虽然家长处理家庭沟通的方式各有不同, 但其动机都是一样的, 即为孩子的最佳利益着想并且(在更含蓄的层面上)维持良好的家庭内部关系。此外,大多数情况下家长会等孩子主动提出通过捐献者受孕这个话题。总体看来,家长致力于构建一个自己和孩子都能接受的通过捐献者受孕的说法。 她们使用不同的策略,例如逐渐披露,限制捐献者的意义,使通过捐献者受孕这一做法合理化。构建一个容易接受的通过捐献者受孕的说法有时候会受到来自社会环境的挑战。本项讨论中,我们将定性系统研究和家庭内部选择性披露及双向性联系起来。